Analysis of The Effect of Market Structure and Firm's Conduct on The Financial Performance of Cigarette Companies in Indonesia 2010-2019 Period (Case Study on Cigarette Companies Listed on The Indonesia Stock Exchange) - Pramono, Ikhlasul Reza (Jurnal Ilmu Ekonomi Terapan, 2022)
The cigarette industry sector is the leading actor of the most significant excise contributor. The potential of this industry experiences several obstacles that cause issues due to the policies set by the Government to maintain public health. These government policies generally affect a firm's profitability due to the changing in market structure and the firm's behavior. In knowing its effect on profitability in more depth, the structure-conduct-performance (SCP) paradigm can be applied in this case. This paradigm emphasizes that changes in market structure and a firm's conduct could later affect the firm's financial performance. Based on this statement, this study aims to analyze the market structure and firm's behavior on the financial performance of cigarette companies listed on the IDX (Indonesian Stock Exchange) during the 2010-2019 period. The independent variables used in this study are the Market Share (MS) and Concentration Ratio (CR4) variables as proxies for the market structure, and the Advertisement to Sales Ratio (ASR) and Capital to Labor Ratio (CLR) variables as proxies for the firm's conduct. The dependent variable used is the firm's financial performance proxied by the Return on Assets (ROA) variable. The analytical method used is the fixed effect model (FEM). FEM select as the analytical method based on the results of the Chow test. The research results in the regression analysis show that the industrial structure proxied by the Market Share (MS) variable has a positive and significant effect on the Return on Assets (ROA) variable. In contrast, the Concentration Ratio (CR4) variable has a negative and significant impact on the Return on Assets (ROA) variable. In contrast, the conduct of the firms, which is proxied by the Advertisement to Sales Ratio (ASR) and Capital to Labor Ratio (CLR) variables, has an insignificant effect on the Return on Assets (ROA) variable.